Cataract surgery and intraocular pressure in glaucoma. Issue 1 (January 2020) - Young, Cara E. Capitena; Seibold, Leonard K.; Kahook, Malik Y.
Abstract : Purpose of review: To review the current literature on the relationship between cataract extraction and intraocular pressure (IOP). Recent findings: Cataract extraction can be an effective IOP lowering treatment for open and closed angle glaucoma as well as ocular hypertension. In comparative trials studying novel micro-invasive glaucoma surgeries in open angle glaucoma, the control group undergoing cataract extraction alone routinely achieved significant reductions in IOP and medication use postoperatively. Data from the Effectiveness in Angle Closure Glaucoma of Lens Extraction (EAGLE) trials have demonstrated that lens extraction is more effective at lowering IOP than peripheral iridotomy in patients with angle closure and should be considered as first line therapy. Additionally, patients in the ocular hypertension treatment study who underwent cataract extraction over the course of follow-up demonstrated significant IOP lowering sustained over 3 years. Summary: Cataract extraction is an effective method to lower IOP in patients with glaucoma. Pressure lowering is more significant in eyes with narrow angles and those with higher baseline IOP levels. In eyes with angle closure, phacoemulsification alone can lower IOP, but when combined with GSL it may be even more effective. Recent large multicenter randomized trials have further elucidated the benefit of standalone cataract extraction to treat mild to moderate primary open angle glaucoma. Prospective and longitudinal studies that systematically investigate the variables that may influence degree and duration of IOP lowering post cataract extraction are lacking.